E-filling dalam Menunjang Efektivitas Kerja Karyawan - Eva Mirza Safitri; Priyanto; Febrina Indrasari (P3I Politeknik Negeri Madiun, 2019)
The development of ICT in various aspects including office management. Now archives have also used technology as a tool to process, access and disseminate and preserve archives. Archives that have use value are now presented and accessed through electronic media. At the Business Administration Department of Madiun State Polytechnic has been acting as an archive processing unit and also manages electronic records. Therefore, in this study wanted to find out how far the use of electronic archives in the Business Administration Department of Madiun State Polytechnic in supporting the effectiveness of employee performance by managing archives. This type of research is a qualitative descriptive study. Where the object of this research is electronic archives in the Business Administration Department of Madiun State Polytechnic. Data collection techniques use observation, interviews and documentation. Data analysis techniques in this study use interactive analysis models. Based on the results of the study showed the use of E-filling has not been able to fully support the work effectiveness of the administrative staff of the Department of Business Administration, Madiun State Polytechnic.